Relationship between anxiety and static and dynamic balance disorder in subjects with cerebrovascular accident (stroke) diagnosis. - Ferreira, Ana Paula Lemos; Barbosa, Danillo (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Background: According to the World Health Organization, cerebrovascular accident (Stroke) is defined as an acute neurological dysfunction that occurs due to a change in the brain circulation, resulting in signs and symptoms that compromise specific brain sites, persisting for more than 24 hours. There is a range of symptoms that stroke causes, in which motor changes become the most evident and feared symptoms by the patient, as they are the causes of several functional limitations, directly interfering with activities of daily living and possibly causing psychological disorders. Anxiety disorder is one of the psychological disorders that the subject after stroke may have. This disorder is characterized as a state of discouragement, distress and fear, which causes a series of symptoms, such as tachycardia, muscle tension, chronic pain, among others. These emotional and physical changes may be beneficial or harmful to the regularization of the disorders that stroke causes. Objective: To analyze the interference of anxiety on the static and dynamic balance of patients diagnosed with stroke. Methods: Fifteen patients with stroke, aged 40 to 80 years, were assessed using the Hospital Anxiety and Depression Scale, Timed Up and Go test for dynamic balance and the Berg Scale for static balance. Data were tabulated in Excel and analyzed using SPSS. Results: Significant values were found for the correlation between anxiety and balance, in which the results analyzed showed that the balance of patients with stroke can be negatively exacerbated due to the anxiety that affects them. Conclusion: It can be concluded from these results that anxiety can alter the balance of stroke patients and thus, it is shown the importance of a multidisciplinary treatment from the first moment to leverage the treatment.